2019
DOI: 10.1080/14787210.2019.1664287
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic and cranberry supplementation for preventing recurrent uncomplicated urinary tract infections in premenopausal women: a controlled pilot study

Abstract: Objectives: To assess efficacy and safety of Bio-Kult Pro-Cyan (BKPro-Cyan), a product containing two strains of Lactobacilli plus cranberry extract, for preventing recurrent UTIs in pre-menopausal adult women. Methods: This was a randomized, double-blind, placebo-controlled pilot study. Subjects received BKPro-Cyan or placebo twice-daily for 26 weeks. The primary endpoint was the proportion of subjects with recurrent UTI at the end of the study. Results: 115 subjects were screened; 90 were enrolled; 81 comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
2
41
0
4
Order By: Relevance
“…The safety and efficacy of a product containing two probiotic strains of Lactobacilli plus cranberry extract was reported for impeding recurrent UTIs in pre-menopausal adult women. After 26 weeks, in a randomized, double-blind, placebo-controlled pilot study, a significantly lower number of women experienced recurrent UTIs (9.1 vs 33.3%), those who were administered with the product as compared to placebo [ 134 ]. In another study, the efficacy and safety of standardized cranberry capsules as prophylaxis in children with recurrent UTI was reported, where children on cranberry compared to the control group experienced significantly lower percentage of recurrent UTIs, with no side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of a product containing two probiotic strains of Lactobacilli plus cranberry extract was reported for impeding recurrent UTIs in pre-menopausal adult women. After 26 weeks, in a randomized, double-blind, placebo-controlled pilot study, a significantly lower number of women experienced recurrent UTIs (9.1 vs 33.3%), those who were administered with the product as compared to placebo [ 134 ]. In another study, the efficacy and safety of standardized cranberry capsules as prophylaxis in children with recurrent UTI was reported, where children on cranberry compared to the control group experienced significantly lower percentage of recurrent UTIs, with no side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Green Tea Extract (Hoshino et al, 1999;Arakawa et al, 2004;Cooper et al, 2005a,b;Reygaert and Jusufi, 2013;Bae et al, 2015) • Reduction of inflammation (Isolauri et al, 2001;Galdeano and Perdigón, 2006;De Vuyst and Leroy, 2007;Cribby et al, 2008;Cadieux et al, 2009;Riaz et al, 2010;Hardy et al, 2013;Kemgang et al, 2014;Di Cerbo et al, 2016;Chikindas et al, 2018;Ng et al, 2018;Koradia et al, 2019) • Competition, reduction of adhesion and virulence…”
Section: Chinese Medicalmentioning
confidence: 99%
“…A recent randomized, double-blind, placebo-controlled pilot study in 81 premenopausal women showed that the administration of Bio-Kult Pro-Cyan (a commercially available product containing probiotic strains (Lactobacillus acidophilus PXN 35, Lactobacillus plantarum PXN 47) and cranberry extract (36 mg/d PACs) twice-daily for 26 weeks, led to significantly lower number of recurrent UTIs compared to placebo (9.1 vs. 33.3%; P = 0.0053) (Koradia et al, 2019).…”
Section: Vaginal Lactobacillimentioning
confidence: 99%
“…The conventional clinical paradigm regarding the use of cranberry materials for UTI prevention is based on the presence of components in human urine as a result of cranberry consumption that prevent infection by preventing E. coli adhesion to uroepithelial cells [4,23,313]. The compounds most often cited as being responsible for the observed anti-adhesive properties of urine are PACs [314] in spite of the current understanding that these compounds are unlikely to be directly excreted into human urine at significant concentrations, if at all [315].…”
Section: A New Paradigm For Uti Prevention With Cranberry Materialsmentioning
confidence: 99%
“…Trials investigating catheter-associated UTIs [319,320] already typically consider the unique microbiota profiles associated with these devices, but must now also consider the impact that cranberry materials may have on both initial patient UT microbiomes and on the development of both catheter biofilms and subsequent UTIs [63,321]. Clinical trials that investigate the concurrent use of cranberry materials and probiotics [313] must consider the possible prebiotic effects of cranberry oligosaccharides on both the existing microbiota and the provided probiotic organisms, as well as the possible colonization of the UT with the probiotic organisms [322,323].…”
Section: A New Paradigm For Uti Prevention With Cranberry Materialsmentioning
confidence: 99%